Mechanical Properties Of Tensile And Bending Strength Analysis In Biocomposite [SAGOO/PMMA] Material - Rosid, Ibnu Abdul; Putra, Ikbal Rizki; Tontowi, Alva Edy (Institut Teknologi Dirgantara Adisutjipto, 2019)
Biocomposite material is a common material used in biomedical application. One of medical problems related to bone restoration which caused by accidents and injuries resulted in fracture bone parts. Biocomposite (Sagoo/PMMA) is being developed as a solution to solve that particular problem. In current research, tensile and flexural strength of sagoo/PMMA is tested and examined. There are correlation between value of tensile strength, value of bending strength, and curing time, with maximum tensile strength and bending strength were achieved by curing the specimen for 12 hours, with the maximum value of tensile strength is 3,337 MPa, and the maximum flexural is 2,653 MPa. The minimum tensile strength was achieved by curing the specimen for 6 hours with minimum value of tensile strength is 1,502 MPa, while the minimum flexural was acquired at curing time for 24 hours with minimum of bending strength is 0,536 MPa